MusE GAs FLOw and wind (MEGAFLOW) VII. A NOEMA pilot program to probe molecular gas in galaxies with measured circumgalactic gas flows. Issue 2 (11th December 2020) - Freundlich, Jonathan; F Bouché, Nicolas; Contini, Thierry; Daddi, Emanuele; Zabl, Johannes; Schroetter, Ilane; Boogaard, Leindert; Richard, Johan
ABSTRACT: We present a pilot program using IRAM's NOrthern Extended Millimeter Array (NOEMA) to probe the molecular gas reservoirs of six $z$ = 0.6–1.1 star-forming galaxies whose circumgalactic medium has been observed in absorption along quasar lines of sight as part of the MusE GAs FLOw and Wind (MEGAFLOW) survey and for which we have estimates of either the accretion or the outflow rate. This program is motivated by testing the quasi-equilibrium model and the compaction scenario describing the evolution of galaxies along the main sequence of star formation, which imply tight relations between the gas content, the star formation activity, and the amount of gas flowing in and out. We report individual carbon monoxide CO(4-3), CO(3-2), and dust continuum upper limits, as well as stacked CO detections over the whole sample and the three galaxies identified with outflows. The resulting molecular gas fractions and depletion times are compatible with published scaling relations established within a mass-selected sample, indicating that galaxies selected through their absorption follow similar relations on average. We further detect the dust continuum of three of the quasars and a strong emission line in one of them, which we identify as CO(4-3). Extending the sample to more galaxies and deeper observations will enable us to quantify how the molecular gas fraction and depletion time depend on the inflow and ouflow rates.